Characteristics and source profiles of atmospheric volatile organic compounds (VOCs) in the heavy industrial province of Northeast China with cruise monitoring - Shang, Yijing; Chen, Weiwei; Bao, Qiuyang; Yu, Yang; Pang, Xiaobing; Zhang, Yanli; Guo, Li; Fu, Jing; Feng, Wei (Frontiers in Environmental Science, 2022)
As key precursors of tropospheric ozone (O3) pollution, volatile organic compound (VOC) pollution and related studies in China are mainly concentrated in developed re-gions or metropolises, while there are few studies on VOC pollution in the heavy in-dustrial base in Northeast China. This study conducted a systematic survey of VOCs’ information for the first time in Jilin Province, covering eight prefecture-level cities, ten major industries (e.g., petrochemical, chemical), and 130 major factories, based on cruise monitoring for two months. The concentrations and compositions (i.e., 65 species) of VOC were measured in real-time. The emission characteristics of VOC, local source profiles, and the ozone formation potential (OFP) were further analyzed to support O3 pollution control in Northeast China. On the provincial scale, the concentrations of total VOC during the monitoring period ranged from 0.03 to 18321.5 μg/m3, and averaged at 607.9 ± 2051.8 μg/m3. Among the prefecture-level cities, Jilin City had the highest concentration level (1938.0 ± 3811.3 μg/m3) given the largest numbers of petrochemical factories, and the lowest level (85.5 ± 48.9 μg/m3) was found in Liaoyuan City. At the industrial scale, the highest (1915.2 ± 1842.6 μg/m3) was detected in the petrochemical industry with a major species of 1,1,2,2-tetrachloroethane. The lowest VOC emission concentration levels were found in the textile industry (57.8 ± 44.6 μg/m3; major species: xylene/ethylbenzene). Local source profiles in various industries were established, and normalized OFP of corresponding species was calculated, which are important parame-ters to evaluate the contribution of different VOC sources to O3 pollution. Combined with provincial industrial structure and future planning, we suggest two major industries in-cluding the chemical industry and petrochemical industry in Changchun City and Jilin City are prior to being optimized to reduce O3 pollution. This study contributes to the knowledge of the characteristics and source profiles of VOC emissions, providing an important reference for the management or control of O3 pollution in Northeast China.